(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
This article presents a literature review of the role played by agricultural cooperatives in influencing farm sustainability and investigates all three empiric dimensions of sustainability in developing and developed countries. In addition, the main goal is linking the empirical findings to the theoretical understanding of cooperatives, in particular members’ heterogeneity.